Recommendations for the Development and Reform of Microtia and Atresia Services. Issue 4 (June 2019) - Mazeed, Ahmed S.; Saied, Samia; Abulezz, Tarek; Youssef, Gamal; Bulstrode, Neil W.
Abstract : Background: The initial step in setting up standardized microtia-atresia service is investigating the current status of the service and comparing this to internationally recognized guidelines or care standards. In many countries, documented information about microtia care is lacking. This study is an initiative to guide reform efforts of national microtia service in any country. The UK care standards for microtia-atresia can be a useful model to help set up a comprehensive microtia-atresia service. Methods: The authors conducted a survey to investigate different aspects of microtia service in Egypt. The major plastic surgery centers (n = 22) were surveyed by a structured questionnaire. The results were compared with the UK care standards for microtia-atresia to identify the aspects that need improvement. Thorough analysis of the main problems in microtia-atresia service is presented. Results: The authors found that microtia service is fragmented between the surveyed centers with 65% of the centers treating less than 10 microtia cases annually. Multiple surgeons are responsible for ear reconstruction in 90% of centers and only 25% of them practise a multidisciplinary team approach. None of the centers uses validated tools of aesthetic or psychological patient-reported outcome measures. Recommendations: These 5 recommendations are the keys to reforming microtia service in any country: (1) Establishing nationally designated centers to concentrate the required expertise. (2) Assigning fewer high-volume surgeons to optimize the surgical outcomes. (3) Providing treatment by experienced multidisciplinary teams. (4) Using validated tools of patient-reported outcome measures. (5) Collecting and keeping standardized records for regular audit and intercenter studies.